The impactful developed PISA-type problems for students' mathematical literacy through the context of Siger tower - Retnawati, Sri; Prahmana, Rully Charitas Indra; Arnal-Palacian, Monica (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2024)
Indonesia's mathematical literacy levels remain low, as evidenced by its poor performance in PISA rankings over the past decade. One contributing factor is the students' unfamiliarity with PISA-type problems, which emphasize content, context, and process skills. The Siger Tower, an iconic landmark in Lampung, offers a multifaceted context encompassing tourism, arts, culture, religion, and education. This study aims to develop valid, practical, and potentially impactful PISA-type mathematics problems using the Siger Tower as context to enhance mathematical literacy. The research employs a design research methodology with two phases: preliminary design and formative evaluation. The formative evaluation phase includes self-evaluation, expert review, one-to-one testing, small group testing, and field testing. Data analysis is conducted using descriptive methods. The study produced ten PISA-type mathematical problems contextualized with the Siger Tower. These problems were validated in terms of content, construct, and language by expert reviewers and through one-to-one testing. Practicality was assessed during small group testing, and potential impacts on mathematical literacy were evaluated during field testing. The findings indicate that the developed problems effectively engage various basic mathematical skills, thereby promoting mathematical literacy.